Psychological symptoms in family members of critically ill patients during the pandemic: a prospective cohort. - Paixão, Miguel Lucas Silva da; Gonçalves, Gabriel Fernandes de; Silveira, Cristhiane de Souza; Santana, Luisa Brehm; Berto, Paula Pinheiro; Azzolin, Karina de Oliveira; Tavares, Juliana Petri (Acta Paulista de Enfermagem, 2025)
Objective: To assess psychological symptoms in family members of critically ill patients during the pandemic. Methods: This is a prospective cohort study with adult family members of patients admitted to the Intensive Care Unit (ICU) of a university hospital, from July 2020 to April 2022, via telephone contact immediately, six and 12 months after discharge from the ICU, collecting sociodemographic data and assessing symptoms of anxiety, depression and post-traumatic stress. To assess symptoms of anxiety and depression, the Hospital Anxiety and Depression Scale was used and for symptoms of post-traumatic stress disorder, the Impact of Event Scale-6 was used. Descriptive and bivariate statistical analyses were performed. Results: After discharge, 37.7% of family members presented symptoms of anxiety and 32.5% of depression. After six months, these rates reduced to 33.3% and 21.9%, respectively, and after one year, to 12.3% and 6.1%, respectively. Moreover, 30.7% of family members reported symptoms of post-traumatic stress after six months, falling to 12.3% at the end of 12 months. The family nucleus experienced higher percentages of anxiety (p<0.001) and depression (p=0.02) in two or more phases of the study. Family members with a previous diagnosis of anxiety/panic (p=0.002) or depression/bipolar disorder (p=0.01) presented higher percentages of depressive symptoms in two or more phases. Conclusion: Female family members experienced more intense psychological symptoms, especially at the time of discharge from the ICU, lasting for up to 12 months in some individuals.